2018
DOI: 10.1111/wrr.2
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone‐based teleconsultation system for the management of chronic pressure injuries

Abstract: We investigated the accuracy of pressure injury evaluation using tele‐devices and examined the concordance between automatically generated recommendations and primary manual recommendations. Caregivers took photos and videos of pressure injuries using smartphones with built‐in cameras and uploaded the media to the application. The wound team evaluated the wound using a specially modified version of the Pressure Sore Status Tool. This was compared with the Pressure Sore Status Tool score assessed during the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…Pak et al . [ 13 ] (2018) identified that patients and caregivers have easy access to smartphones and their applications. They also found that it is quite accurate for the assessment of physical symptoms of the patients as compared to the on-site assessment by a physician.…”
Section: Discussionmentioning
confidence: 99%
“…Pak et al . [ 13 ] (2018) identified that patients and caregivers have easy access to smartphones and their applications. They also found that it is quite accurate for the assessment of physical symptoms of the patients as compared to the on-site assessment by a physician.…”
Section: Discussionmentioning
confidence: 99%
“…Plataforma mobile de uso paciente para mensuração de feridas e documentação pela captura de imagens Khong et al 21 Evaluating an iPad app in measuring wound dimension: A pilot study Observacional prospectivo Plataforma mobile de uso profissional para mensuração de feridas pela análise de imagem Salomé et al 22 Multimedia application in a mobile platform for wound treatment using herbal and medicinal plants Metodológico Plataforma mobile de uso profissional para tratamento de feridas com plantas medicinais Jaspers et al 23 The FLIR ONE thermal imager for the assessment of burn wounds: Reliability and validity study Metodológico Plataforma mobile de uso profissional para avaliação de feridas de queimaduras Nair et al 24 Increasing productivity with smartphone digital imagery wound measurements and analysis Observacional prospectivo Plataforma mobile de uso profissional e paciente para mensuração de feridas a partir de imagens digitais ao fotografar, documentar e medir. Pak et al 25 A smartphone-based teleconsultation system for the management of chronic pressure injuries…”
Section: Projeto-pilotounclassified
“…Some patients themselves were using mobile phones to obtain images of their DFUs prior to their foot clinic visits so that they could show the status of their ulcers earlier. Although the initial studies on use of mobile phones for monitoring DFUs were not very promising[ 22 ], subsequent studies show encouraging results[ 23 - 25 ].…”
Section: History Of Digital Archiving Of the Dfu Photographsmentioning
confidence: 99%